2014
DOI: 10.1037/lhb0000061
|View full text |Cite
|
Sign up to set email alerts
|

Young children’s understanding that promising guarantees performance: The effects of age and maltreatment.

Abstract: Two studies, with 102 nonmaltreated 3- to 6-year-old children and 96 maltreated 4- to 7-year-old children, examined children’s understanding of the relative strengths of “I promise,” “I will,” “I might,” and “I won’t,” to determine the most age-appropriate means of eliciting a promise to tell the truth from child witnesses. Children played a game in which they chose which of 2 boxes would contain a toy after hearing story characters make conflicting statements about their intent to place a toy in each box (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
(63 reference statements)
2
20
0
Order By: Relevance
“…Our verbalized commitment, ‘I will not peek at the toy’, removed the word ‘promise’ from the commitment and significantly reduced cheating rates for children from 3 to 5 years of age. This supports Heyman et al's suggestion that the lack of effect with young children may have been related to their difficulty with understanding the word ‘promise’ (Astington, , ; Lyon & Evans, ) and indicates that, at least among preschool children, the word ‘promise’ is not required to induce such a social obligation. This is particularly interesting considering previous literature has emphasized how promising is important because it allows for one to show their intention to follow through with the behavior (Bussey, ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our verbalized commitment, ‘I will not peek at the toy’, removed the word ‘promise’ from the commitment and significantly reduced cheating rates for children from 3 to 5 years of age. This supports Heyman et al's suggestion that the lack of effect with young children may have been related to their difficulty with understanding the word ‘promise’ (Astington, , ; Lyon & Evans, ) and indicates that, at least among preschool children, the word ‘promise’ is not required to induce such a social obligation. This is particularly interesting considering previous literature has emphasized how promising is important because it allows for one to show their intention to follow through with the behavior (Bussey, ).…”
Section: Discussionsupporting
confidence: 82%
“…However, prior studies have indicated that young children struggle to understand the implications of the word ‘promise’ (Astington, , ). For example, Lyon and Evans () found that 3‐to‐5‐year‐old children showed greater understanding when the words ‘I will’ were used compared to ‘I promise’, and that ‘I will’ was understood at a younger age. Similarly, Astington () found that young children used the words ‘I will’ more often than ‘I promise’ when acting out scenarios with an experimenter where they had to assure the experimenter they would follow through with a given action.…”
Section: Introductionmentioning
confidence: 99%
“…Given that maltreated children tend to exhibit lower scores on both executive functioning measures (e.g., Beers & De Bellis, 2002) and measures of vocabulary (Lyon & Evans, 2014) than non-maltreated children, at least when compared with middle-and upper-middle class children typically studied in developmental research, it was useful to examine how maltreated children would respond. Moreover, we sought to replicate the effects found in Study 1.…”
Section: Studymentioning
confidence: 99%
“…In fact, developmental work has shown that 3-to 10-year-old French children view future-directed speech acts (''I will do it") and assertions with a predictive content (''It will be done") as promises (Bernicot & Laval, 1996). However, under some circumstances, such as when statements containing ''promise" and ''will" provide conflicting evidence (e.g., regarding the location of a hidden toy), older but not younger children trust ''promise" statements more than ''will" statements (Lyon & Evans, 2014). To further investigate whether the word ''promise" is necessary to elicit task commitment in our study, we conducted a follow-up study with 3-and 5-year-olds where we elicited commitments without asking children to promise.…”
Section: P Kanngiesser Et Al / Journal Of Experimental Child Psychomentioning
confidence: 99%